Proceedings of the 2014 ACM Symposium on Principles of Distributed Computing 2014
DOI: 10.1145/2611462.2611489
|View full text |Cite
|
Sign up to set email alerts
|

Optimal gossip with direct addressing

Abstract: Gossip algorithms spread information in distributed networks by having nodes repeatedly forward information to a few random contacts. By their very nature, gossip algorithms tend to be distributed and fault tolerant. If done right, they can also be fast and message-efficient. A common model for gossip communication is the random phone call model, in which in each synchronous round each node can PUSH or PULL information to or from a random other node. For example, Karp et al. [FOCS 2000] gave algorithms in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Consider the problem of disseminating information in a large-scale distributed system: a source node in the network has some information that it wants to share/aggregate/reconcile with others. This fundamental problem has been widely studied under various names, e.g., information dissemination (e.g., [5]), rumor spreading (e.g., [8]), global broadcast (e.g., [20]), one-to-all multicast, information spreading (e.g., [6]), and gossip (e.g., [21]).…”
Section: Arxiv:161106343v3 [Csdc] 17 Dec 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the problem of disseminating information in a large-scale distributed system: a source node in the network has some information that it wants to share/aggregate/reconcile with others. This fundamental problem has been widely studied under various names, e.g., information dissemination (e.g., [5]), rumor spreading (e.g., [8]), global broadcast (e.g., [20]), one-to-all multicast, information spreading (e.g., [6]), and gossip (e.g., [21]).…”
Section: Arxiv:161106343v3 [Csdc] 17 Dec 2018mentioning
confidence: 99%
“…For graphs modeling social networks Doerr et al [11,12] show a Θ(log n) time bound for solving broadcast. For the case of direct addressing, Haeupler and Malkhi [21] show that broadcast can be performed optimally in O(log log n) rounds. Information dissemination has been studied in random geometric graphs by Bradonjić et al [4], in wireless sensor networks networks by Boyd et al [3] and Farach-Colton et al [14], in mobile adhoc networks by Fernandez-Anta et al [13] and in dynamic graphs by Sarwate and Dimakis [28], Gandhi et al [17], and Giakkoupis et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fault tolerant broadcast algorithms have also been studied extensively, especially in complete networks and in synchronous environments, where the focus has been on weak types of failures such as (probabilistic) message failures and initial node crashes. Essentially, it has been shown that there exist broadcast protocols that can overcome such faults with a relatively little penalty [21,23,24,35,38,39,43,60].…”
Section: Context and Related Workmentioning
confidence: 99%
“…Journal version update: Motivated by the conference version of this paper [1], Haeupler and Malkhi [21] improved our bound and presented an elegant algorithm that solves the problem we study here in O(log log n) rounds together with a macthing lower bound. Nevertheless we think our work contributes to the understanding of the gossiping process and may be useful in extension of the model to general graphs.…”
Section: Our Contributionmentioning
confidence: 99%